Influence of mental health on the well-being status among Malaysian adults before and during COVID-19 pandemic. Issue 1 (2nd January 2023) - Cheah, Whye Lian; Law, Leh Shii; Samy, Alexander Lourdes; Chua, Bee Seok; Siau, Ching Sin; Fitriana, Mimi; Bono, Suzanna Awang; S, Vighnarajah; Low, Wah Yun
ABSTRACT: The coronavirus disease (COVID-19) pandemic has affected the well-being of individuals worldwide. Due to the scarcity of information in the Malaysian context, this study aimed at investigating the changes in well-being before and during the Movement Control Order (MCO) in Malaysia and its association with mental health status. This cross-sectional study was part of a Malaysian non-probabilistic online survey on psychosocial well-being in Malaysia, under the Personal and Family Coping with COVID-19 Global South Research Consortium. A total of 543 respondents (≥18 years old) were recruited using snowball sampling. A validated self-administered questionnaire for assessing sociodemographic characteristics, well-being, anxiety, boredom, and loneliness was circulated on social media platforms (such as Facebook, Twitter, and WhatsApp) and emails. Paired samples t-test, chi-square test, and multinomial logistic regression analyses were applied during data analysis. Results revealed significant changes in the mean scores of well-being, anxiety, boredom, and loneliness before and during MCO (p < 0.05). When comparing with no change in the well-being group, changes in boredom were less likely to be observed in the decreased well-being group ( Adj OR = 0.874; p = 0.003) but were more likely to be observed in the group with increased well-being ( Adj OR = 1.110; p = 0.002). The findings indicated that the pandemic did not necessarily create adverse effects. Instead, a different perspective is offered, which can be used as a public health strategy to help individuals cope with their mental health needs more positively.